Effect of 1.9-MeV electron irradiation on characteristics of reactively-pressed TiB₂–TiС ceramic composites - Totsky, I.N.; Popov, A.Yu.; Makara, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Considered in this paper is the effect of electron irradiation on the phasestructural
state and micromechanical characteristics of reactively- and nonreactivelypressed
TiB₂–TiС composite ceramic materials. It is shown that reactively-pressed
specimens after irradiation demonstrate a growing tendency to phase formation, which
considerably affects proceeding of relaxation processes in them. This special feature of
reactively-pressed ceramics can improve radiation resistance of construction materials